Linguistic Approach To The Problem Of Dyslexia In Uzbek-Speaking Children - Akbarova, Zuhro; Xalimov, Baxtiyorjon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
In this article, the issue of dyslexia in Uzbek-speaking children and its symptoms are discussed in detail. Additionally, linguistic approaches to identifying and preventing dyslexia are examined, along with reflections and insights on addressing this issue.